Wasail al-Ta'allum bi al-Bithaqah al-Mushawwarah li al-Thullab Mu'aqiin Dzihni fi Itqan Mufradat al-Lugah al-Arabiyah - Dwi Shinta Khoirin Nisa' (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2022)
Educational services are provided to all children both normal children and children with special needs. In other words, educational services do not distinguish physical, emotional, social and intellectual. And children with special needs should be given different educational services because in general children with special needs have obstacles in following the development of science, technology and art and varying needs. Therefore, the use of learning media can help teachers in delivering learning materials. This research aims to describe the learning media used by teachers in SLBN Gending in teaching vocabulary to students with intellectual disabilities. Research data is collected through observations, interviews, and document studies. Based on the data obtained, it was found that the implementation of image card media carried out by teachers there are four steps, namely displaying images, saying vocabulary, writing vocabulary, and understanding vocabulary. And the implication is that the use of pictorial media is more effective for students with intellectual disabilities. They follow learning actively and enjoyably.